Optimizing Healthcare Delivery: Analyzing the Relationship Between Inpatient Medical Record Return Time and Service Effectiveness at Ciremai Hospital - Syahr, AlfiSyahr; Mustara, Mustara (Jurnal Medisci, 2023)
The medical record installation must maintain medical records correctly and appropriately, including the return of medical records. According to the Ministry of Health (2006), the standard for returning inpatient medical records is ≤ 2x24 hours after completion of treatment. Meanwhile, the standard of service effectiveness in the form of time for providing outpatient medical records according to Kepmenkes number 129 of 2008 is ≤ 10 minutes. The purpose of the study was to determine the relationship between inpatient medical record return time and service effectiveness. The research method used is quantitative with a cross-sectional design. The population is 220 medical records of post-inpatient patients who are controlled outpatients at Ciremai Hospital during January 2022. The total sample is 145 using the Slovin formula with the purposive sampling technique. Univariate analysis using frequency distribution and bivariate analysis using the Spearman rank correlation test are used because the data is not normally distributed. The results show that the average time to return inpatient medical records is 115,86 hours, the fastest time is 24 hours, and the longest time is 360 hours. The average service effectiveness in the form of outpatient medical record provision was 222,26 minutes; the fastest time was 3 minutes; and the longest time was 710 minutes. The Spearman rank correlation coefficient is 0,418 with a p-value of 0,000 ≤ 0,05. The conclusion is that there is a relationship with moderate correlation strength between inpatient medical record return time and service effectiveness, with a value of 0,418.